Asteraceae Plants as Sources of Compounds Against Leishmaniasis and Chagas Disease - Moraes Neto, Roberval Nascimento; Setúbal, Ruth Flávia Barros; Higino, Taciana Mirely Maciel; Brelaz-de-Castro, Maria Carolina Accioly; da Silva, Luís Cláudio Nascimento; Aliança, Amanda Silva dos Santos (Frontiers in Pharmacology, 2019)
Leishmaniasis and Chagas disease cause great impact on social and economic aspects of people living in developing countries. The treatments for these diseases have been based on the same regimen for over 40 year, thus, there is an urgent need for the development of new drugs. In this scenario, Asteraceae plants (a family widely use in folk medicine worldwide) are emerging as interesting sources of new trypanocidal and leishmanicidal compounds. Herein, we provide a non-exhaustive review about the activity of plant-derived products from Asteraceae with inhibitory action towards Leishmania spp. and T. cruzi. Special attention was given to those studies aiming the isolation (or identification) of its bioactive compounds. In relation to anti-Leishmania compounds, ent-3-α-hydroxy-kaur-16-en-18-ol (from Aldama discolor; syn. Viguiera discolor Baker), ferulic acid and rosmarinic acid [both from Pluchea carolinensis (Jacq.) D.Don] showed high selective index (SI> 15). In addition, ferulic acid, rosmarinic acid, ursolic acid (Baccharis uncinella DC.) were efficient to treat experimental leishmaniasis. The most active compound against T. cruzi were ent-15β-senecioyl-oxy-kaur-16-en-19-oic acid (Baccharis retusa DC.; SI= 50) and ethyl caffeate (Calea uniflora Less.; SI= 12.95); while deoxymikanolide (Mikania micrantha) and (+)-15-hydroxy-labd-7-en-17-al (Aristeguietia glutinosa Lam.) showed in vivo anti-T. cruzi action. It is also important to highlight that several plant-derived products (compounds, essential oils) from Artemisia plants have shown high inhibitory potential against Leishmania spp., such as Artemisinin and its derivatives. In summary, these compounds may help the development of new effective agents against these neglected protozoans diseases.